Comparative analysis of strain parameter acquisition based on Cave strain and GPS observation. Issue 1 (September 2020) - Hu, Leyin; Lv, Taiwen; Yan, Rui; Fan, Zhiyong; Xu, Bin
Abstract: A set of three-component extensometers are installed on the Xibozi Seismic Station in Yanqing District, Beijing. The layout of the extensometers is an isosceles triangle, and the observation is the amount of expansion and contraction of each side, which is then converted into the strain value of each side. In this paper, the regional crustal strain parameters were calculated based on the observations of the extensometers and the continuous GPS observations around Xibozi Sesimic Staion. From two aspects of observation at the same site and different scales, the ground strain information reflected by the two observation methods is compared and analyzed. From the strain parameters calculated by a single point (extensometers) and the strain parameters calculated by the triangular surface observation (GPS) with different specifications, the overall Beijing area is in the context of tensile strain. However, there is a gap of several orders of magnitude between the two results, which may be related to the artificial operation of the pre-processes such as zero drift and step removal of the instrument's strain observation data.